Electric commercial vehicles: Practical perspectives and future research directions. (March 2016) - Margaritis, Dimitris; Anagnostopoulou, Afroditi; Tromaras, Alkiviadis; Boile, Maria
Abstract: The existence of an efficient, sustainable and environmentally friendly "green" freight transport system requires several challenges to be addressed to reduce negative externalities. Over the last few years, the efforts for technological improvements and innovation in transport have been intensified and fleets of vehicles using renewable sources is the new trend for public authorities, non-profit organizations and many private companies promoting sustainable development. This paper studies the use of electric commercial vehicles within the spectrum of "green" transport, provides a critique of their key technical specifications and identifies the main operating conditions that influence their effectiveness. It is an attempt to exploit challenges and contemplate policy adjustments for the wider take-up of electric commercial vehicles in daily transport operations within the EU area. Highlights: Fully charged overnight with several short day sessions is a usual charging scheme. Research effort about operational problems utilizing EVs is at an early stage. In practice, fleets of both conventional and EVs are used for transport services. A wider uptake of EVs requires both financial and regulatory incentives. Future research should integrate both environmental and operational objectives.